Self-medication with antimicrobials in children: a study in tertiary care hospital, Odisha, India - Ganguly, Sristi; Pankaj, Kiran C.; Satpathy, Saroj K. (International Journal of Contemporary Pediatrics, 2020)
Background: Antimicrobial resistance is emerging as global threat to health, the injudicious use being linked to multiple reasons namely parental misconceptions, easy drug availability and previous experiences. Children, due to frequent illnesses, are victims of this misuse and more than fifty percent of these drugs are self-medicated by caregivers. This study attempts to assess the trends associated with self-medication with antimicrobials in children and the factors associated with it. Methods: This is a hospital based cross-sectional study, among pediatric outpatients aged 1 month to 14 years, in SCBMCH and SVPPGIP, Cuttack, during March 2019 to September 2019. A structured dichotomous questionnaire was administered to caregivers, including details of socio-demography and antimicrobials self-medicated. A pilot study was done for period of 1 month, and questionnaire accordingly modified. Data was analysed with Chi- square test and percentages, using SPSS 18. Results: Among the 300 patients studied, prevalence of self-medication with antimicrobials was 21%. Most patients self-medicated on pharmacists’ advice (44.4%), commonest reason being similar illness previously (41.3%). Fever (31.7%) and cold cough (28.6%) were usual conditions, with Azithromycin being most frequently administered. 54% of cases self-medicating antimicrobials, had errors of dose or duration, with 27% reporting side-effects. Child’s age (p=0.042), father’s age (p=0.044), mother’s age (p=0.002), chronic illness in child (p=0.002) and type of family (p=0.011) were significantly associated with antimicrobial self-medication in children. Conclusions: The high prevalence of self-medication with antimicrobials mandates need to educate parents and enforce laws regarding illegal dispensing of these drugs, to reduce the threat from resistance.